2016
DOI: 10.4172/2167-0234.1000186
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Perceptual Biasness in Debit Cards of Indian Banks

Abstract: banking products and services efficiently and effectively. The new private and foreign bankers on the basis of adoption of new technological services like plastic cards, personal computer banking, electronic funds transfer, internet banking can able to connect maximum number of customers in spite of having less physical presence. Now public sector banks are equally trying to move towards electronic banking, which leads to the remarkable development with respect to its operational efficiency, customer services,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The study found that customers with larger balance in their account know more about credit cards and their awareness level is found to be high and Low awareness category comprised of more of customers with short period customership. Prasad, S. in (2016) [9] study on, "Consumers' Perceptual Biasness in Debit Cards of Indian Banks" to explore recent issue related to the debit card and the preference of customers towards different types of debit cards of different banks. The study based on Primary collected through questionnaire of sample taken from 400 respondents.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…The study found that customers with larger balance in their account know more about credit cards and their awareness level is found to be high and Low awareness category comprised of more of customers with short period customership. Prasad, S. in (2016) [9] study on, "Consumers' Perceptual Biasness in Debit Cards of Indian Banks" to explore recent issue related to the debit card and the preference of customers towards different types of debit cards of different banks. The study based on Primary collected through questionnaire of sample taken from 400 respondents.…”
Section: Review Of Literaturementioning
confidence: 99%
“…(2015) [6] Kerala   Raza, S. A. & et al (2016) [7] Andhra Pradesh   Sudhagar, S. (2012) [8] Tamil Nadu   Prasad, S. in (2016) [9] Orissa   Dhanda, K. (2016) [10] Haryana   Bijapurkar, & et. lt. (2014) [10] Delhi & NCR   Patil, S. in (2014) [11] Maharashtra   Hooda, N. (2016) [14] Haryana   Sharma, A.…”
Section: Authormentioning
confidence: 99%
See 1 more Smart Citation